2010
DOI: 10.1002/cphc.201000892
|View full text |Cite
|
Sign up to set email alerts
|

Photoionization of C7H6 and C7H5: Observation of the Fulvenallenyl Radical

Abstract: Species of the composition C 7 H n are known intermediates in combustion processes.[1] One out of five C 7 H 5 isomers, fulvenallenyl, was recently computed to be a resonance-stabilized radical [2] expected to be long-lived and to play an important role in the formation of soot and polycyclic aromatic hydrocarbons.[3] Thus, its structural and thermochemical characterization is relevant for the combustion community. A C 7 H 5 species was previously observed in a toluene flame, [4] but could not be unambiguously… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
58
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
10

Relationship

7
3

Authors

Journals

citations
Cited by 55 publications
(66 citation statements)
references
References 21 publications
8
58
0
Order By: Relevance
“…[2][3][4][5] In 2009 it was found that a subsequent hydrogen abstraction could lead to fulvenallenyl radical (the global C 7 H 5 minimum), which was unambiguously identified by measuring its mass-selected threshold photoelectron spectrum (ms-TPES). [6][7][8] The products arising from the dissociation of substituted benzyl radicals, however, are less well understood. The decomposition dynamics of xylenes are also relatively unexplored, despite their prevalence in gasoline.…”
Section: ) Introductionmentioning
confidence: 99%
“…[2][3][4][5] In 2009 it was found that a subsequent hydrogen abstraction could lead to fulvenallenyl radical (the global C 7 H 5 minimum), which was unambiguously identified by measuring its mass-selected threshold photoelectron spectrum (ms-TPES). [6][7][8] The products arising from the dissociation of substituted benzyl radicals, however, are less well understood. The decomposition dynamics of xylenes are also relatively unexplored, despite their prevalence in gasoline.…”
Section: ) Introductionmentioning
confidence: 99%
“…Ionisation energies have been determined from vibrationally resolved photoelectron spectra for several open-shell species ranging from allyl [22] and propargyl [23] to indenyl (C 9 H 7 ) [24], cyclopropenylidene [25] and fulvenallenyl [26]. In the case of allyl [2728] and propargyl [29] they are in excellent agreement with high-resolution laser studies.…”
Section: Introductionmentioning
confidence: 87%
“…. Atomic hydrogen can add at the 4 and 6 positions in HCCCCCH 2 CCH with small barriers (1–4 kcal mol −1 ) to produce open‐chain C 7 H 5 radicals that can isomerize to the C 7 H 5 minima fulvenallenyl in a process that is ∼100 kcal mol −1 exothermic with barriers over 20 kcal mol −1 below the energy of the entrance transition states. The vibrationally excited C 7 H 5 adducts can also dissociate to form the propargyl radical plus diacetylene or the resonance‐stabilized radicals i ‐C 5 H 3 or n ‐C 5 H 3 plus acetylene, with barriers more than 10 kcal mol −1 below the entrance transition states.…”
Section: 36‐heptatriyne + Hmentioning
confidence: 99%